ChemInform Abstract: A Multifunctional Biomaterial with NIR Long Persistent Phosphorescence, Photothermal Response and Magnetism. Issue 50 (November 2016) - Wu, Yiling; Li, Yang; Qin, Xixi; Qiu, Jianrong
Abstract: Multifunctional phosphors Zn3 Ga2 SnO6 :Cr 3+, Nd 3+, Gd 3+ with near‐IR long persistent phosphorescence, photothermal response, and magnetism are prepared by solid state reaction of stoichiometric amounts of ZnO, Ga2 O3, SnO2, Cr2 O3, Gd2 O3, and Nd2 O3 (1350 °C, 4 h).